2022
DOI: 10.1038/s41392-022-01174-w
|View full text |Cite
|
Sign up to set email alerts
|

Cancer metastasis chemoprevention prevents circulating tumour cells from germination

Abstract: The war against cancer traces back to the signature event half-a-century ago when the US National Cancer Act was signed into law. The cancer crusade costs trillions with disappointing returns, teasing the possibility of a new breakthrough. Cure for cancer post-metastases still seems tantalisingly out of reach. Once metastasized, cancer-related death is extremely difficult, if not impossible, to be reversed. Here we present cancer pre-metastasis chemoprevention strategy that can prevent circulating tumour cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 200 publications
0
9
0
Order By: Relevance
“…Likewise, CTCs also gained substantial hype as an important marker to understand the pathology as well as the efficacy of drugs against diseases. The pharmaceutical relevance of CTCs has been highlighted with recent research showcasing the role of different factors related to CTCs to understand their adhesions at the secondary metastatic sites [ 213 ]. Organoid culture platforms generated from CTCs have been used to understand the pharmacotypic signatures related to tumors and use them as a tool for personalized therapeutics domains [ 214 ].…”
Section: Pharmaceutical Contextmentioning
confidence: 99%
“…Likewise, CTCs also gained substantial hype as an important marker to understand the pathology as well as the efficacy of drugs against diseases. The pharmaceutical relevance of CTCs has been highlighted with recent research showcasing the role of different factors related to CTCs to understand their adhesions at the secondary metastatic sites [ 213 ]. Organoid culture platforms generated from CTCs have been used to understand the pharmacotypic signatures related to tumors and use them as a tool for personalized therapeutics domains [ 214 ].…”
Section: Pharmaceutical Contextmentioning
confidence: 99%
“…Based on this principle, a novel chemoprevention paradigm for cancer metastasis has recently been proposed. 17 It differs from conventional strategies in that it emphasises the use of drugs to block the vascular adhesion of CTCs, thereby preventing the initiation of the lethal metastatic cascade.…”
Section: Vascular Adhesion Of Metastatic Tumour Cellsmentioning
confidence: 99%
“…As vascular adhesion is the first step in initiating metastasis in distant target organs, the leading cause of death in many cases of primary malignancy, its inhibition is a good strategy. Based on this principle, a novel chemoprevention paradigm for cancer metastasis has recently been proposed 17 . It differs from conventional strategies in that it emphasises the use of drugs to block the vascular adhesion of CTCs, thereby preventing the initiation of the lethal metastatic cascade.…”
Section: Ec–tumour Cell Interactionmentioning
confidence: 99%
“…Recent studies have shown that tumor-derived exosomes are involved in the formation of pre-metastatic niches (PMNs), which promote a favorable environment for the arrival and survival of metastatic cells at secondary sites [ 9 12 ]. It is crucial to PDAC’s metastasis that the PMNs shield the circulating tumor cells (CTCs) from apoptosis when they reach the metastatic location [ 13 ]. Exosomes released by cancer cells facilitate the development of PMNs by facilitating angiogenesis, stromal cell remodeling, extracellular matrix (ECM) remodeling, and oncogenic reprogramming [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%